A Population-Based Clinical Trial of Irinotecan and Carboplatin. (23rd April 2009) - Lau, Derick; Huynh, Minh; Johl, Jewel
Abstract : Purpose . Phase I trials of anticancer drugs are commonly conducted using the method of modified Fibonacci. We have developed a population-based design for phase I trials of combining anticancer drugs such as irinotecan and carboplatin. Patients and Methods . Intrapatient dose escalation of irinotecan and carboplatin was performed according to a predetermined schema to reach individual dose-limiting toxicity (DLT) in 50 patients with solid tumors refractory to previous chemotherapy. The individual toxicity-limiting dose levels were analyzed for normal distribution using the method of Ryan-Joiner and subsequently used to determine a population-based maximum tolerated dose (pMTD). For comparison, a simulation study was performed using the method of modified Fibonacci. Results . The most common dose-limiting toxicities (DLTs) included neutropenia (58%), thrombocytopenia (16%), and diarrhea (8%). The frequency of individual toxicity-limiting dose levels of 50 patients approximated a normal distribution. The dose levels associated with individual limiting toxicities ranged from level 1 (irinotecan 100 mg/m 2 and carboplatin AUC = 4 mg/mLx min) to level 8 (irinotecan 350 mg/m 2 and carboplatin AUC = 6). The pMTD was determined to be dose level 3 (150 mg/m 2 for irinotecan and AUC = 5 for carboplatin). In contrast, the MTD was determined to be dose level 4 (200 mg/m 2 for irinotecan and AUC 5 for carboplatin) by modified-Fibonacci simulation. Conclusions . The population-based design of phase I trial allows optimization of dose intensity and derivation of a pMTD. The pMTD has been applied in phase II trial of irinotecan and carboplatin in patients with small-cell lung cancer.